Molecular detection of flavivirus in blood serum of rodents captured in Yucatán, Mexico - Torres-Castro, Marco; Poot-Pérez, Martha; Moguel-Lehmer, Carlos; Reyes-Hernández, Bibiana; Panti-May, Alonso; Noh-Pech, Henry; Hernández-Betancourt, Silvia; Medina-Espinosa, Nicolás; Puerto, Fernando I. (Revista de Investigaciones Veterinarias del Perú, 2017)
The aim of this investigation was to study the presence of flaviviruses in rodents from Yucatan, Mexico, by the Polymerase Chain Reaction (PCR) in the semi-nested variant. Ninety rodents were captured (87 Rattus rattus, two Heteromys gaumeri and one Mus musculus), and blood samples were collected. The resulting serum samples were grouped into 30 triads (pools). The semi-nested PCR yielded a positivity frequency of 33.3% (10/30). El objetivo de la presente investigación fue estudiar la presencia de flavivirus en roedores de Yucatán, México, mediante una prueba de Reacción en Cadena de la Polimerasa (PCR), en su variante semi-anidada. Se capturaron 90 roedores (87 Rattus rattus, dos Heteromys gaumeri y un Mus musculus) y se les recolectó una muestra de sangre. Las 90 muestras de suero resultantes fueron agrupadas en 30 triadas (pooles). La PCR semianidada arrojó una frecuencia de positividad del 33.3% (10/30).